LITERATURE REVIEW ON THE USE OF THERAPY OZONE IN MEDICAL AND AESTHETICS - Farahatun Nabilah Mat Isa; Mohd Hafiz Safiai (Journal of Islamic, Social, Economics and Development, 2018)
This article discusses on the usage of ozone therapy as an alternative treatment in medical and aesthetics. Originally, ozone was used to disinfect bacteria in the operation room and drinking water treatment before its use is developed for industrial purpose, as well as an alternative therapy in treating the chronic illnesses in medicine. However, ozone’s specification is considered harmful to the patient either in medical field or any other treatment because of its toxicity. This article purposes to examine the previous studies on the effectiveness of ozone therapy in medical treatment. Besides, this article also will discusses effects of the therapy on humans. This article is a qualitative research which is using document analysis approach. The results found that although ozone therapy managed to treat various diseases, but it will adversely effect the patient if unsuitable dose used during the therapy. Hence, this article expected to disclose and provide knowledge to the patients and medical practitioners in particular, as well as academicians and public in general about the usage of ozone as a therapy in medical and aesthetics.